Open surgical repair of giant hepatic artery aneurysm - Maged Metias, MD; Eva Liu, MD; Michael Troncone, MD; Mohammed Alsulaimani, MD; David Szalay, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Hepatic artery aneurysms (HAAs) are visceral artery aneurysms with a significant risk of mortality upon rupture. HAAs can be treated with open or endovascular repair. The choice of treatment modality depends on aneurysm anatomy, adequacy of visceral collaterals, and overall health status of the patient. This case report describes the successful repair of a giant 14.9-cm HAA through open aneurysm resection and end-to-end anastomosis of the distal common hepatic artery to the gastroduodenal artery. The patient recovered postoperatively with no complications and normal liver function. This case report also reviews other giant HAAs that have been reported in literature.